Non-conventional interventions to prevent gonorrhea or syphilis among men who have sex with men: A scoping review - Tran, Julien; Fairley, Christopher K.; Bowesman, Henry; Aung, Ei T.; Ong, Jason J.; Chow, Eric P. F. (Frontiers in Medicine, 2022)
Objectives We assessed nonconventional interventions that did not traditionally focus on increasing condom use and/or testing among men who have sex with men (MSM) and the evidence for these interventions. Methods Guided by the Participants, Concept and Context (PCC) framework, we searched five online databases from inception to 9 August 2021 for original research on interventions that do not focus on increasing condom use and/or testing to prevent gonorrhoea and/or syphilis in MSM. Two researchers screened titles and abstracts to assess eligibility, reviewed articles’ full text and resolved discrepancies through discussion. We charted relevant study information, and the included studies were critically appraised. Results Of 373 articles retrieved, 13 studies were included. These studies were conducted in Australia (n=3), Belgium (n=2), China (n=3), the Netherlands (n=1) and the US (n=4). Two randomised controlled trials (RCTs) of doxycycline as pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP) reduced any STI incidence (gonorrhoea, syphilis, or chlamydia), but only doxycycline PEP significantly reduced syphilis incidence. Six studies of interventions that facilitated self-collection, self-examination, and self-testing, found varied evidence for gonorrhoea and/or syphilis prevention. Four RCTs and one single-arm trial examined the efficacy of mouthwash, but the evidence remains inconclusive on whether mouthwash use can prevent transmission between men. Conclusion We found evidence for doxycycline PEP in reducing syphilis incidence, evidence on the use of mouthwash to prevent gonorrhoea transmission between men remains inconclusive. More evidence is needed for interventions that do not focus on increasing condom use and/or testing to prevent gonorrhoea and/or syphilis.